Conceptual model of intelligent command and control for UAV cluster based on OPM - ZHOU Huanhuan, ZHAO Guolin, DU Xinglin (Zhihui kongzhi yu fangzhen)
Intelligent command and control is the inevitable trend of future UAV cluster combat command and control. Based on object-process methodology, a conceptual model of intelligent command and control for UAV cluster is proposed in this paper. Under the unified view, the physical objects, information, environment and process involved in the intelligent command and control of UAV cluster are abstractly described. The top-level conceptual model of intelligent command and control of UAV cluster, SD1-level amplification model as well as SD2-level sub-process model is designed and constructed by means of operational-functional unified specification modeling(OFUS). The model is tested and verified by the function of OPCAT software, and the result proves the logical feasibility of the model.